Influence of jet discharge velocity profile on CFD simulation of pump-around jet mixing tank - Thanwa Jorakit; Natthanon Phaiboonsilpa; Apinan Namkanisorn; Phisan Ponpo; Eakarach Bumrungthaichaichan; Santi Wattananusorn (My University, 2018)
The present paper shows the effect of jet discharge velocity profile (or jet nozzle configuration) on CFD simulation of an open 45° inclined side entry pump-around jet mixing tank. The CFD model was carefully developed by using appropriate grid arrangement, boundary conditions, and numerical methods. The two different jet discharge velocity profiles, including top hat and fully developed profiles, were simulated by using the inlet mass flow rate of about 0.22 kg·s -1 . The overall mixing times and normalized concentration profiles predicted by two different jet discharge velocity profiles were compared with the previous reliable experimental data. The results revealed that the different jet discharge velocity profiles resulted in different jet flow and mixing patterns inside the vessels.
Keywords: Cyclone Separators and Fluid Dynamics